Filozofie mediów w serialu Black Mirror - Wiatr, Przemysław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
The article seeks to answer the following question: To what extent is it possible to philosophize about the media through media images? This problem is analysed using the example of selected episodes of the anthological series Black Mirror. The author contrasts the theoretical insights of 20th- and 21st-century philosophers (Baudrillard, Flusser, Sloterdijk, Adorno, Horkheimer, Žižek) with examples of their pictorial implementation in Black Mirror episodes. The text explores two themes: the problem of appropriation of reality by the media, and issues related to the mechanisms of mass culture and possible ways to criticize them.